Phylogeny and Differential Gene Expression Profile of IL-1R8 in Normal Dog Tissue - Turin L.; Bianchessi L.; Filipe J.; Inglesi A.; Riva F. (Assiut University, Faculty of Veterinary Medicine, Department of Animal Medicine, 2022)
Interleukin-1 Receptor 8 (IL-1R8) is a transmembrane protein of the IL-1 receptor family and represents an important regulator of the balance of innate and inflammatory responses. Depending on the immunological insult, IL1-R8 protects from the immunopathology or impairs the protective immune response against the insult. The expression pattern of IL-1R8 in dog tissues is unknown. Given the relevance of inflammatory diseases in dog, the aims of this study were to identify the sequence, analyze the phylogenesis and investigate the differential expression and distribution of IL-1R8 in a wide panel of non-pathologic tissues and organs by means of quantitative Real-Time PCR and uncover species-specific peculiarities. In Canis lupus familiaris, the IL1-R8 gene maps on chromosome 18, and includes ten exons. We first compared the coding sequence of dog IL-1R8 with sequences of other carnivors. Phylogenetic analysis revealed that IL-1R8 shares significantly high sequence homology with IL-1R8 of other canids particularly fox, sharing a common progenitor. Our study demonstrated that IL-1R8 is highly expressed in pancreas, considerably expressed in kidney, heart, liver, skeletal muscle, thymus, salivary gland, lymph node and lung. Interestingly, the expression pattern disclosed a unique profile for canine tissues when compared to tissues from other animal’s species. Imbalance of pro-inflammatory response leads to a vicious loop whither pro-inflammatory signaling and injury sustain each other and booster the disease. Therefore, it is crucial to investigate key regulator molecules such as IL-1R8, which functions both in homeostasis and disease and has potential to be a valid diagnostic, prognostic and therapeutic biomarker.